Synthesis and characterization of methyl methacrylate - glycerol hydrogels by polymerization in acid medium - Laura Trujillo-Vargas (Memoria Investigaciones en Ingeniería)
Hydrogels were prepared from methyl methacrylate, glycerol, and sulfuric or citric acid. A novel route for the synthesis of crosslinked materials using unconventional initiators was evaluated using a 23 factorial experimental design. Effects of independent variables (polymerization time, type, and acid concentration) were statistically analyzed through ANOVA. The synthesis route includes condensation, free-radical and transesterification reactions with modifications of the polymer chemical properties such as the formation of a crosslinking polyester with polymethylmethacrylate (PMMA) and improvement of the mechanical and thermal properties of the hydrogel. A polymerization time of 4-hour produced the highest amount of material when 1.37 g sulfuric acid was used and 3.46 g when citric acid was added. The polymer synthesized with citric acid has a swelling rate up to 214.6%, compared with the materials produced with sulfuric acid that reach up to 31.3% of water absorption.